Problem-Based Learning in a Medical School: Implementations Challenges - Rezende,Kátia Terezinha Alves (2020)
Abstract: Introduction: Considering an integrated curriculum that is guided by dialogical competence according to the National Curriculum Guidelines, the Systematized Educational Unit (UES) and the Professional Practice Unit (UPP) constitutes the curriculum of a medical course in a municipality in the countryside of the state of São Paulo, Brazil. Problem-Based Learning (PBL) is used in the UES and the problematization is used in the Professional Practice Unit as teaching methodologies, seeking an organization that leads to a training that is coherent with the public health sector and the national education scenario. The UES is the focus of this study because we observed that there are divergences among teachers regarding their role as tutors. Thus, we observed that the teaching methodology currently employed at Famema led us to some questions: Do the teachers consider themselves qualified to work with the PBL method? How do evaluations contribute to the teaching-learning process? Thus, this study aimed to analyze the teachers’ understanding of their ability to work with the PBL and the relevance of evaluations for the teaching-learning process in the UES. Method: This is an exploratory-descriptive study with a qualitative approach. Data collection was carried out using a semi-structured interview with teachers who work with the 1st to 4th years in the UES of the medical course, and the selection of the participants was carried out from a non-probabilistic sample of intention, totaling 16 teachers, including four teachers of each of the first four years of the course. The analysis of the data was performed by Content Analysis in the thematic modality, which allowed the definition of two thematic axes: Challenges for teacher training and Potentials and limits of the implemented evaluation process. Results: The trajectory of the PBL in the teaching-learning process from the point of view of teachers showed us a variety of understandings. As for teacher training, weaknesses were identified in the development of the tutoring process, and that the strategies used for training need to be reviewed regarding their implementation and the inclusion of the professionals into the process. Regarding the evaluation, it was observed that the teachers demonstrate difficulties in carrying out an evaluation of the students while integrating the affective, cognitive and psychomotor dimensions. Conclusion: Therefore, regardless the time of the curriculum implementation, Permanent Education should constitute a powerful space for teacher training and process management.